Analysis of Essential Learning Materials in the Automotive Body Subject at Vocational Schools: Delphi Technique - Amir Fatah; Kir Haryana; Yoga Guntur Sampurno (STAI Hubbulwathan Duri, 2025)
Excessive learning materials can hinder the teaching and learning process by overwhelming students, reducing motivation, and impairing knowledge retention. In vocational education, irrelevant content may further contribute to graduates' lack of industry-aligned competencies, limiting their employability. This study aims to identify essential learning materials for the automotive panel and body frame course based on urgency, continuity, relevance, and industry application. A modified Delphi technique was used to gather expert consensus through a survey involving 21 automotive body and frame repair professionals from the automotive manufacturing and repair industry in Yogyakarta, Indonesia. The questionnaire, developed based on the automotive engineering curriculum, utilized a four-point Likert scale. Data collection was conducted via Google Forms and analyzed using descriptive statistics in SPSS software. Industry experts identified key learning materials essential for vocational students, including MIG-GMAW welding procedures, repairing damaged panels made of iron, aluminum, plastic, or fiberglass, applying putty, and assessing panel surface quality after putty application. These materials were deemed critical for aligning vocational training with industry requirements. The findings emphasize the importance of refining learning content to enhance student competency and employability. By prioritizing industry-relevant skills, vocational educators can improve instructional effectiveness and better prepare graduates for the workforce. This study provides valuable insights for curriculum developers to ensure that training programs meet industry standards, ultimately enhancing student learning outcomes.